Mind the Gap: Convergence of Technology and Technology of Convergence in Italian Regions, 1982-2001 - Francesco Quatraro (European Regional Science Association (ERSA), 2006)
The paper investigates the patterns of Total Factor Productivity (TFP) convergence across Italian regions, in the period 1982-2001. According to the main theoretical approaches, two different concepts of convergence may be devised, strongly intertwined. Beta-convergence applies when poor, lagging behind countries tend to grow faster than the rich and leading ones, while sigma-convergence refers to the reduction of the cross-regional dispersion of the productivity index over time. We start from the distinction between "first" and "second" capitalism, representing two areas interested by different and idiosyncratic evolutions of the industrial structure after the World War II. The former area consists of North-western regions, while the latter basically refers to North-eastern and Adriatic regions. While North-eastern regions were characterized by higher TFP levels in 1982, the "second capitalism" regions showed up sensible lower levels. The hypothesis of convergence of TFP found strong econometric support, as we could reject both the hypothesis of no-mean reversion and that of no convergence (Lichtenberg, 1996). The evidence abut sigma convergence is even more striking, as TFP dispersion has been decreasing since 1985, with a speeding up in the second half of the 1990s. We argue that this pattern of convergence is the result of catching up process in which laggards are still able to deploy the growth potential of the post-fordist model of industrialization, while leading regions, according to the Wolff's law, have slowly exhausted those opportunities. Empirical evidence suggests that this is occurring through the routinization of innovative activity and the support of R&D carried out within Universities and public labs. This witnesses the key role of both innovation and knowledge spillovers from academia to the business system and stresses once more the need to sustain the provision of funds to the public research system.
Keywords: 330